Effects of Magnetic Stimuli on Vigilance: A Heart Rate Variability Analysis. Issue 3 (2017) - Cui, Huanhuan; Qi, Hongzhi; Ming, Dong; Tian, Miao; Backer, Robert Allan; Ke, Yufeng; Wei, Jinwen; Zhou, Peng; Wang, Xuemin
No abstract available